PHEVs Park as Virtual UPFC - F. R. Islam; H. R. Pota (Institute of Advanced Engineering and Science, 2012)
Unified power flow controllers (UPFCs) are FACTS devices which can fulfil multiple power-flow control objectives, such as the need for reactive shunt compensation, phase shifting and series compensation. However, as they are quite expensive, they are not widely used. In this paper, the potential of a plug-in hybrid electric vehicle (PHEV) in a vehicle-to-grid (V2G) mode of operation using a PHEV charging station to provide a low-cost solution to the design of a virtual UPFC is explained. A third-order dynamic battery model is used to represent the PHEV, and the simulations carried out demonstrate that a PHEV has the potential to work as a virtual UPFC to improve power quality. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1673